2022
DOI: 10.3389/fpubh.2022.959921
|View full text |Cite
|
Sign up to set email alerts
|

Different components of air pollutants and neurological disorders

Abstract: The harmful effects of air pollution can cause various diseases. Most research on the hazards of air pollution focuses on lung and cardiovascular diseases. In contrast, the impact of air pollution on neurological disorders is not widely recognized. Air pollution can cause various neurological conditions and diseases, such as neural inflammation, neurodegeneration, and cerebrovascular barrier disorder; however, the mechanisms underlying the neurological diseases induced by various components of air pollutants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Several studies have suggested a relationship between lung stressors such as air pollution, silicosis, or the pulmonary microbiome and the CNS 14 , 29 , 30 . The lung-brain axis is at least partially mediated by inflammation and/or oxidative stress 14 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested a relationship between lung stressors such as air pollution, silicosis, or the pulmonary microbiome and the CNS 14 , 29 , 30 . The lung-brain axis is at least partially mediated by inflammation and/or oxidative stress 14 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested a relationship between lung stressors such as air pollution, silicosis, or the pulmonary microbiome and the CNS 14 , 29 , 30 . The lung-brain axis is at least partially mediated by inflammation and/or oxidative stress 14 , 29 . Although microglial activation is one of the triggers of AD, the present study revealed no statistically significant changes in microglial activation in pathological analysis and no inflammation or oxidative stress based on the relative gene expression of brain tissue 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Neurological Disorder: Mounting evidence suggests that air pollution can adversely affect the central nervous system and increase the risk of neurological disorders. Dusty particulate matter and toxic gases can enter the brain through the olfactory nerves or systemic circulation, leading to neuroinflammation, oxidative stress, and neuronal damage (Ying et al, 2013;Li et al, 2017;Azarpazhooh and Hachinski, 2018;Gładka et al, 2018;Jia et al, 2018;Thomson, 2019;Gu et al, 2020;Kim et al, 2020;Xue et al, 2021;Fu et al, 2022;Sirbu et al, 2022). Studies have linked air pollution exposure to neurodevelopmental disorders in children, cognitive decline in adults, and an increased risk of neurodegenerative diseases like Alzheimer's and Parkinson's.…”
Section: Methodsmentioning
confidence: 99%
“…93 Only small lipophilic molecules, such as oxygen (O 2 ) and carbon dioxide (CO 2 ), diffuse freely through it, although other gases such as NO 2 /NO x , VOCs, O 3 and SO 2 can also reach the brain via diffusion through the lung epithelial and vascular endothelial layers, and neuronal olfactory nerve and disruption of the BBB by inducing oxidative stress and the expression of pro-inflammatory molecules. 94 These cells in the brain express transporter proteins to facilitate the transport of nutrients by their concentration gradients. The major pathways of vascular dysfunction that are related to neurodegenerative diseases include degradation of the BBB, hypoperfusion–hypoxia, and in more advanced cases, endothelial metabolic dysfunction.…”
Section: Pm and Ufps In The Cnsmentioning
confidence: 99%